Analysis of The Performance of Three Main Roads In Cilegon When Controlling The Transportation During The Covid-19 Pandemic For The Prohibition Of Homecoming For Eid Al-Fitr 2021 - Bethary, Rindu Twidi; Intari, Dwi Esti; Budiman, Arief; Haibarizqi, Nastheissya Ansi (JURUSAN TEKNIK SIPIL, 2023)
The Covid-19 Handling Task Force together with government officials, have announced the release of the Circular of the Head of the Covid-19 Handling Task Force No. 13 of 2021 concerning the elimination of homecoming during the month of Ramadan and Eid al-Fitr 1442 Hijri during 6 - 17 May 2021. This policy aims to anticipate a surge in the flow of domestic tourists which can protect the public from the transmission of the covid-19 virus. This research was conducted to determine traffic performance on the three main roads of Cilegon City during the homecoming control period. From the data from the survey conducted for three days, an analysis of the traffic movements that occurred and the level of road service was carried out by calculating the degree of saturation (DJ) and free flow speed. The results showed that the highest movement occurred on weekdays with the highest vehicle volume of 4429 vehicles, with the highest destination occurring in the direction of the city of Serang and the highest type of vehicle being a motorcycle, then for the average Degree of Saturation of the three main roads of Cilegon City by 0,46 and an average free flow speed of 50.75 km/hour, so that it can be concluded that the level of service for the three main roads of the city of Cilegon is in category A, namely good service conditions where vehicles can run smoothly even though they are sometimes hampered by low traffic volume and density. This is because there are roadblocks that limit people's movements and reduce the volume of vehicles.